2020
DOI: 10.1148/radiol.2020192866
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Blunt Cerebrovascular Injury: Experience Over a 10-year Period at a Level I Trauma Center

Abstract: Background: Blunt cerebrovascular injury (BCVI) is associated with increased stroke and mortality risk. However, the most appropriate follow-up strategy remains uncertain. Purpose:To better understand the natural history of BCVI and help define the most optimal timing and length of follow-up imaging. Materials and Methods:In this retrospective HIPAA-compliant study, data from all patients treated for BCVI at a level I trauma center between April 1, 2005, and June 30, 2015, were reviewed. For patients with at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 22 publications
0
18
0
4
Order By: Relevance
“…Of injuries that may improve or resolve, a prior study reported that 76% of changes occur within 1 month of the initial injury, and 24% occur by 3 months [46]. Beyond 3 months, no additional improvement or resolution generally occurs [46]. Short term follow-up CTA within 3 months may have the highest diagnostic yield in assessing for injury change, which may also determine whether continuation or cessation of antithrombotic treatment is required following discharge [14].…”
Section: Treatment and Follow-upmentioning
confidence: 99%
See 2 more Smart Citations
“…Of injuries that may improve or resolve, a prior study reported that 76% of changes occur within 1 month of the initial injury, and 24% occur by 3 months [46]. Beyond 3 months, no additional improvement or resolution generally occurs [46]. Short term follow-up CTA within 3 months may have the highest diagnostic yield in assessing for injury change, which may also determine whether continuation or cessation of antithrombotic treatment is required following discharge [14].…”
Section: Treatment and Follow-upmentioning
confidence: 99%
“…After this initial period, follow-up studies indicate that healing of the vessel is inversely associated with initial injury grade [45]. However, the majority of BCVIs, up to 84%, may show improvement or complete resolution over time [46]. Of injuries that may improve or resolve, a prior study reported that 76% of changes occur within 1 month of the initial injury, and 24% occur by 3 months [46].…”
Section: Treatment and Follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients experiencing craniocervical trauma are at risk of devastating injuries, including traumatic cerebrovascular injury and traumatic brain injury 1 2. Traumatic cerebrovascular injury occurs in 3–20% of patients following craniocervical trauma and is a frequent cause of morbidity and mortality 1 3–5. Timely diagnosis and management can prevent devastating neurological complications 5.…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic cerebrovascular injury occurs in 3–20% of patients following craniocervical trauma and is a frequent cause of morbidity and mortality 1 3–5. Timely diagnosis and management can prevent devastating neurological complications 5. With improvement in techniques, expertise, and evidence for endovascular interventions, neurointerventionalists play an increasingly important role in the treatment of patients with traumatic cerebrovascular injury 6–9.…”
Section: Introductionmentioning
confidence: 99%